Virtual laboratory lessons in enzymology. Issue 5 (30th June 2020) - Quesada, Víctor
Abstract: The recent COVID‐19 pandemic has led to widespread lock‐down strategies that force universities to perform all educational activities remotely. In this context, laboratory lessons pose a significant challenge. Here, I present an on‐line tool that simulates the kinetics of chemical reactions. Enzymatic mechanisms can be easily modeled and followed through time. In addition, professors can customize the interface to hide the reaction mechanism. This setting will force students to design virtual experiments to uncover the mechanism and obtain the relevant enzymatic parameters. While some of the skills developed in a practical lesson cannot be simulated, this tool can be used to teach students important concepts about data acquisition and processing.